2015
DOI: 10.1037/pas0000027
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Cultural Loss Scale: Development and psychometric evaluation.

Abstract: The Cross-Cultural Loss Scale (CCLS), a measure of loss associated with crossing national boundaries, was developed across 2 samples of international students. With Sample 1 (N = 262), exploratory factor analyses were used to select the 14 CCLS items and to determine 3 factors: Belonging-Competency (α = .87), National Privileges (α = .68), and Access to Home Familiarity (α = .72). With Sample 2, confirmatory factor analyses (N = 256) cross-validated the 3-factor oblique model as well as a bifactor model. Cronb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 44 publications
3
38
0
1
Order By: Relevance
“…This percentage is enough indicated that grade point academic of Timorese student is studying in Indonesia has been impacted by self-adjustment. This finding is on the same truck or direction of previous research that conducted by Wang et al, (2015) that international student needs to adjust them self to a new culture, society, environment and new circumstance including learning and academic ethos. It will facilitate them to reach an optimal grade point academic.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This percentage is enough indicated that grade point academic of Timorese student is studying in Indonesia has been impacted by self-adjustment. This finding is on the same truck or direction of previous research that conducted by Wang et al, (2015) that international student needs to adjust them self to a new culture, society, environment and new circumstance including learning and academic ethos. It will facilitate them to reach an optimal grade point academic.…”
Section: Discussionsupporting
confidence: 71%
“…The international student faces stressful experiences because of loss-cross culture means they struggle to adjust and to let their familiar richness of things (personal relationships, home, family, country, and educational system environment) gone from them. At the same time, international student struggles to adjust to a new culture, society, environment and new circumstance including learning and academic ethos (Wang et al, 2015). Meanwhile, they struggle to embrace new people, culture, society, and environment in the positive mainstream because all these experiences enrich them to be a flexible person to increase social, academic, self-efficacy, psychology and cultural adjustment and create a spirit of acculturation (Smith & Khawaja, 2011).…”
Section: Self-adjustmentmentioning
confidence: 99%
“…Considering a person’s individual identity without considering his sociocultural narrative and background is insufficient for examining his internalized homophobia ( Fivush, Habermas, Waters, & Zaman, 2011 ; Kim et al, 2006 ). The Chinese concept of self is always defined by relationship, which is termed a social-oriented tendency ( Wang, Wei, Zhao, Chuang, & Li, 2015 ). In Chinese communities, social expectations are deeply intertwined and integrated into one’s self-concept, and the social pressures surrounding gay men may also become a unique factor in their internalized homophobia ( Kim et al, 2006 ; Yang, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although international students’ psychological distress has been widely examined, it is not until recently that a handful of studies have begun to explore invariance of these distress measures (K. T. Wang, Wei, Zhao, Chuang, & Li, 2014; Wei, Wang, & Ku, 2012).…”
mentioning
confidence: 99%
“…T. Wang, Wei, Zhao, Chuang, & Li, 2014; Wei, Wang, & Ku, 2012). For instance, K. T. Wang et al (2014) developed the Cross-Cultural Loss Scale and validated its measurement properties by conducting cross-sectional measurement invariance testing between two samples of international students.…”
mentioning
confidence: 99%